FUTURE TENSE: THE COMING WORLD ORDER/ Gwynne Dyer - Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2013)
“‘Terrorism’ is what we call the violence of the weak, and we condemn it; ‘War’ is what we call the violence of the strong, and we glorify it – Sydney Harris. With this quote the reader is introduced to developments worldwide over the past twenty years and their future implications.